eROSITA studies of the Carina nebula - Sasaki, Manami; Robrade, Jan; Krause, Martin G.H.; Knies, Jonathan; Tsuge, Kisetsu; Pühlhofer, Gerd; Strong, Andrew (Astronomy & Astrophysics, 2024)
Context. During the first four all-sky surveys eRASS:4, which was carried out from December 2019 to 2021, the extended Roentgen Survey with an Imaging Telescope Array (eROSITA) on board the Spektrum-Roentgen-Gamma (Spektr-RG, SRG) observed the Galactic H II region, the Carina nebula. Aims. We analysed the eRASS:4 data to study the distribution and spectral properties of the hot interstellar plasma and the bright stellar sources in the Carina nebula. Methods. The spectral extraction regions of the diffuse emission were defined based on the X-ray spectral morphology and multi-wavelength data. The spectra were fit with a combination of thermal and non-thermal emission models. The X-ray bright point sources in the Carina nebula are the colliding wind binary η Car, several O stars, and Wolf-Rayet (WR) stars. We extracted the spectra of the brightest stellar sources, which can be well fit with a multi-component thermal plasma model. Results. The spectra of the diffuse emission in the brighter parts of the Carina nebula are well reproduced by two thermal models, a lower-temperature component (∼0.2 keV) and a higher-temperature component (0.6-0.8 keV). An additional non-thermal component dominates the emission above ∼1 keV in the Central region around η Car and the other massive stars. Significant orbital variation in the X-ray flux was measured for η Car, WR 22, and WR 25. η Car requires an additional time-variable thermal component in the spectral model, which is associated with the wind-wind collision zone. Conclusions. Properties such as temperature, pressure, and luminosity of the X-ray emitting plasma in the Carina nebula derived from the eROSITA data are consistent with theoretical calculations of emission from superbubbles. This confirms that the X-ray emission is caused by the hot plasma inside the Carina nebula that has been shocked-heated by the stellar winds of the massive stars, in particular, of η Car.
CRIS-Team Scopus Importer:2025-02-04
Keywords: HII regions; ISM: bubbles; ISM: structure; stars: massive; X-rays: ISM; X-rays: stars